Efectos del fuego en la vida Silvestre de Florida y su hábitat - Martin B. Main; George W. Tanner (EDIS)
WEC-137-S, a 5-page illustrated fact sheet by Martin B. Main and George W. Tanner, is the Spanish language version of WEC137/UW132: Effects of Fire on Florida’s Wildlife and Wildlife Habitat. It addresses concerns regarding the use of prescribed fire to manage wildlife habitat in Florida. Includes references. Published by the UF Department of Wildlife Ecology and Conservation, January 2009.